Community‐based genetic study of Parkinson's disease in Estonia. (20th August 2020) - Muldmaa, Mari; Mencacci, Niccolò Emanuele; Pittman, Alan; Kadastik‐Eerme, Liis; Sikk, Katrin; Taba, Pille; Hardy, John; Kõks, Sulev
Abstract : Objective: To examine the genetic variability of Estonian Parkinson's disease (PD) patients using an ongoing epidemiological study in combination with a genetic analysis. Methods: This study was a community‐based genetic screening study of 189 PD patients, and 158 age‐ and sex‐matched controls screened for potential mutations in 9 PD genes using next‐generation sequencing and multiplex ligation‐dependent probe amplification method. Different clinimetric scales and questionnaires were used to examine PD patients and assess clinical characteristics and severity of the disease. Results: The overall frequency of pathogenic PD‐causing variants was 1.1% (2/189), and any rare genetic variant was present in 21.2% (40/189) of the patients and in 8.2% (13/158) of the controls ( P < .05). Variants of unknown significance accounted for 10.6% (20/189). Frequency of any GBA variant among PD patients was 10.1% (19/189) and in controls 3.8% (6/158). The frequency of any GBA variant in PD compared to controls was significantly higher ( P = .035; OR 2.82; CI 95% 1.05‐8.87). Burden of rare variants was not different between patients and controls. Also, a novel GBA pathogenic variant p.E10X was detected. Conclusion: Among different genetic variants identified in Estonian PD patients, GBA variants are the most common, while an overall pathogenic variant frequency was 1.1%.